THE EFFECT OF CORE CAPITAL, QUALITY OF GOVERNANCE IMPLEMENTATION ON THE PROFITABILITY OF RURAL BANKS IN KALIMANTAN WITH CREDIT RISK AS A MEDIATION VARIABLE - Budi Rahman; Irene Rini Demi Pangestuti (RADJA PUBLIKA, 2024)
Rural banks (BPR) have an important role in supporting financial inclusion, especially in remote areas. This study examines the effect of core capital and governance quality on profitability with credit risk as a mediating variable at BPRs in Kalimantan during the period 2016–2023. Using quantitative methods with secondary data, the research sample consisted of 51 BPRs with 326 observations after outlier adjustment. The analysis was conducted with SPSS 26.0 using path analysis two-fold regression. The results of the study show that the first regression shows that core capital has a significant negative effect on credit risk (sig. 0.002; coefficient -0.172), the quality of governance implementation as measured by the decrease in the value of the governance composite has a significant positive effect on increasing credit risk (sig. 0.086; coefficient 0.094). The second regression shows that core capital has a significant positive effect on profitability (ROA) (sig. 0.023; coefficient 0.112), while the quality of governance implementation as indicated by the decrease in the value of the governance composite is not significant (sig. 0.338; coefficient 0.115). Credit risk was found to have a significant negative effect on profitability (sig. 0.000; coefficient -0.368). The Sobel test shows that credit risk is able to mediate the relationship between core capital and profitability (sig. 0.00380 < 0.10; Coef 0.063), and credit risk can also mediate the relationship between the quality of governance implementation and profitability (sig. 0.0933 < 0.10; Coef -0.034).